The utility of leukergy test in gastroenteritis with Campylobacter in children - Simona-Gabriela Vlaic; Laura-Mihaela Ion; Ionela Alina Ganta; Smaranda Diaconescu; Cristiana Tanase (Amaltea Medical Publishing House, 2023)
Gastroenteritis with Campylobacter has proven in the last decade to be one of the most common causes of bacterial enteritis in children. Objectives. The objective of the current study was to highlight the usefulness of using the leukergy test, a test characterized by the aggregation capacity and increased adhesiveness of leukocytes in the case of bacterial infections, in order to establish as early as possible, the bacterial etiology of campylobacteriosis compared to the time it takes to gather other bacteriological evidence. Materials and methods. This paper was based on a single center prospective case-control study conducted between June 2020 and May 2021 at Ponderas Academic Hospital, which involved 45 children hospitalized with medium and severe forms of gastroenteritis with Campylobacter Jejuni, and a control group of 40 children who are clinically and biologically healthy. The property of aggregation, adhesiveness of leukocytes in peripheral blood of the 85 children included in the research was studied using the leukergia test. The results of the leukergia test were subsequently compared with other acute phase reactants, collected from the same blood sample: total leukocyte count (WBCC), total neutrophil count (NEUT), C-reactive protein (CRP). Results. Sensitivity, Specificity and Positive Predictive Value had values of: 93.3%, 82.50%, 85.71% for leukergy (%); 93.3%, 85%, 87.5% for WBCC with normal values; 88.89%, 82.5%, 85.11% NEUT and 95.56%, 97.5%, 97.7% for CRP. Conclusions. The leukergy test is a good predictor in the early establishment of bacterial etiology in the case of gastroenteritis with Campylobacter Jejuni, being a quick and effective test price quality ratio. The leukergy test can be of real help through the additional information that it brings also in medical centers that do not have advanced investigative capabilities.